Design of Single Switch Rectifier for Electric Vehicle Battery Charger Application - Indra Nisja (2002)
A single switch rectifier was developed in this thesis, which has continuous input and output currents. The design and implementation of a single switch three-phase multi resonant rectifier delivering 147 Vdc at 2.2 kW output has been carried out. By the use of a multi resonant scheme, the IGBT operates with zero current switching and the diode operates with zero voltage switching. This multi-resonant rectifier with a single transistor is capable of drawing a higher quality input current waveform, good power factor and low stresses on the semiconductor devices. Buck type converter was used for the power stage, and hence the output voltage is lower than the input voltage. Moreover, these rectifiers have a wide load range with low stress on semiconductor devices. Simulation and experimental results are presented. The total harmonic distortion (THD) of the line current is less than 5% and the system efficiency is about 90% at 25% of maximum load. The single switch rectifier using multi resonant zero current switching has been simulated using OrCad release 9.1 software for 25% of maximum load. A good agreement between simulation and experimental results has been achieved.